PENINGKATAN KOMPETENSI MAHASISWA PADA MATA KULIAH ELEKTRONIKA DAYA MELALUI IMPLEMENTASI E- LEARNING UNTUK MENYIAPKAN CALON GURU SMK BERTARAF INTERNASIONAL - Ali, Muhammad; Hartoyo, Hartoyo (Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
ABSTRACTThis study aims at improving the students competence on electronic power system course through the implementation of E-Learning to prepare teacher candidates for vocational school with international standard. The reserach method was action reserach with E-Learning. The implementation of E-learning and classroom were conducted simultaneously. The planned action, excuted action and devloped action referred to Elliot’s model of action research. In order to achieve better result, several modification and adaptation were formulated based on need and condition. The reserach result showed that E-learning implementation on electronic power system course had successfully implemented on even semester in the academic year of 2011/2012. The site of E-learning for electronic power system can be accessed at http://besmart.uny.ac.id. The learning process with E-learning gave a positive contribution for both E-learning system and the learning process. It was indicated by the increase of student attandence, students’attention, task completion, students’respond, more time for learning, and task exercise. The learning process with e-learning also gave positive influence on the students’ability which was indicated on the score improvement of pre-test and post-test from 57,11 into 71,4.   Keywords: e-learning, electronic power system, action reserach